Genotoxic effects induced by beta-myrcene following metabolism by liver HepG2/C3A human cells - Orlando, Juliana Botinhon [UNESP]; Silva, Brian Ogushi [UNESP]; Pires-Cunha, Camila Lehnhardt [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Gaivão, Isabel O’Neill de Mascarenhas; Maistro, Edson Luis [UNESP] (Taylor & Francis, 2019)
Beta-myrcene [or myrcene (1,6-Octadiene, 7-methyl-3-methylene-)] and the essential oils containing this monoterpene have been widely used in cosmetics, detergents, and soaps, and as flavoring additives for food and beverages. Due to the potentially high level of human exposure to beta-myrcene, and absence of studies involving its genotoxicity in human cells, the aim of this study was to investigate the cytotoxic and genotoxic potential of this terpenoid in non-metabolizing cells (leukocytes) and liver metabolizing cells (HepG2/C3A cells). Prior to the genotoxic assessment by the comet and micronucleus (MN) assays, a range of beta-myrcene concentrations was tested in a preliminary MTT assay. Regarding the MTT assay, the results showed cytotoxic effects for leukocytes at 250 µg/ml and higher concentrations, while for HepG2/C3A cells, absence of cytotoxicity was noted relative to all tested concentrations (after 24 hr exposure). Thus, the concentrations of 2.5, 10, 25, 50, and 100 µg/ml for leukocytes, and 2.5, 100, and 1000 µg/ml for HepG2/C3A cells were selected for subsequent assays. Genotoxicity evaluation demonstrated significant DNA damage in the comet assay and significant chromosomal abnormalities including nucleoplasmic bridges and nuclear buds in HepG2/C3A cells at beta-myrcene concentrations of 100 and 1000 µg/ml. Under our experimental conditions, caution is recommended in the use of beta-myrcene, since this compound produced genotoxic effects especially after metabolic activation using human HepG2/C3A cells, which may be associated with carcinogenic and teratogenic effects previously reported in the literature.
Keywords: 1-Octadiene; 7-methyl-3-methylene; clastogenic/aneugenic effects; comet assay; micronucleus test; MTT assay; Myrcene; terpene